A new amphibious species of the genus Scolopendra Linnaeus, 1758 (Scolopendromorpha, Scolopendridae) from the Ryukyu Archipelago and Taiwan - Tsukamoto, Sho; Hiruta, Shimpei F.; Eguchi, Katsuyuki; Liao, Jhih-Rong; Shimano, Satoshi (Zootaxa, 2021)
In Japan and Taiwan, five valid species of the genus Scolopendra Linnaeus, 1758 have been described: S. morsitans Linnaeus, 1758, S. subspinipes Leach, 1816, S. mutilans Koch, 1878, S. japonica Koch, 1878, and S. multidens Newport, 1844. Recently, an undetermined species was found in the Ryukyu Archipelago and Taiwan. Using molecular phylogenetic analyses with mitochondrial COI and 16S rRNA and nuclear 28S rRNA and 18S rRNA genes as well as conventional morphological examination, we successfully discriminated this sixth species as an independent lineage from S. subspinipes, S. mutilans, and other named congeners from East and Southeast Asia. Therefore, the species was described as S. alcyona Tsukamoto & Shimano, sp. nov. Several situational evidences suggest that this species prefers streamside environments and exhibits amphibious behavior.